A Modern Space Situational Awareness System - Thomas M. Jackson; Holland, H.; Tuparev, G.; Steinbatz, M.; Promper, W.; Weinzinger, D.; Doeberl, E.
We, Tuparev AstroTech in partnership with Astro Syteme Austria, present a next-generation Space Situational Awareness (SSA) system currently being created for the tracking and characterisation of satellites and space debris in the age of big-data astronomy. Our SSA system will be based on the image processing of white-light images to detect streaks produced by satellites and space debris. These images will be obtained by a network of 20-30 custom and in-house built SSA observatory stations, which will be made operational worldwide over the coming decade. The system will use machine learning algorithms to choose the optimal part of the sky to observe at any given moment, analyse the incoming data on-site and in real-time, and deliver various standardised data packages and science-quality images to be stored on a bespoke central archive capable of storing petabytes of data. With this system, we aim to cover a greater geographical and celestial area than any previous SSA system, to create a scalable system that is both fast and efficient, and to enable access to orders of magnitude more storage capacity and information than any other system currently available, commercial or governmental.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture